The Correlation Between Project Learning Models and Student Activities in Online Learning for Innovative Learning Model Courses - Manasikana, Oktaffi Arinna; Af’idah, Noer; Bakar, Abu; Andalia, Nurlena; Safmila, Yuliani (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2023)
Based-project learning system provides many opportunities to access material as much as possible, so the learning can be optimum. The innovative learning model course is a compulsory basic course for prospective teachers, that requires students to be active in learning the material. This study aims to determine the effectiveness of project learning on student activity in innovative learning models course. The research conducted was used the experimental method. The results showed that the activeness of students in the activity was included in the successful category, the result is 72.7% and student activity in understanding the innovative learning model was included in the successful category, it is 63.6%. Student responses to project learning are included in the very successful category 81.8%. Mastery of student concepts has increased from 45.8 to 85.8. The results of statistical research using partial regression correlation analysis techniques and multiple correlations show a significant positive relationship between project learning and learning effectiveness with a correlation coefficient (ry1) = 0.201 and there is a significant positive relationship between student activities in innovative learning models and learning effectiveness with correlation coefficient (ry2) = 0.759, and there is a significant positive relationship between project learning and student activities together with learning effectiveness with correlation coefficient (ry12) = 0.769. Based on the results of these studies, it can be concluded that the effectiveness of learning can be increased through project learning and student activities.